Perspectives of Ethical and Moral Decline on Dysfunctional Family of Bundrens: An Interpretative Study of As I Lay Dying by William Faulkner: Unveiling the Ethical and Moral Decline within the Dysfunctional Bundren Family (Journal of Advances and Scholarly Researches in Allied Education, 2019)
William Faulkner’s novel “As I Lay Dying” recounts the theme of decline especially, regarding ethical and moral decline in the American South. Faulkner himself was a victim of that particular decline which he artistically shows through the tale of the Bundren family. The Bundrens pass through a series of shocking and dreadful events throughout the novel. In the ongoing process of the events ethical and moral decline of the Bundrens and of society are largely presented through the physical decline of bodies and nature. What is striking in the novel, the development of it only occurs with a corpse, rather the dead body of the matriarch of the family. The dead body itself reminds the members of the family of acrid taste of death. All the major characters of “As I Lay Dying” are devoid of any religious value or sentiment, causing moral decline among them. This paper aims at demonstrating how man is losing his ethical and moral sense and his action gives rise to perversion, thus, cutting him from the main stream of the society. Through this article I have ventured to prove that man is made of stern stuff and even though temporarily he may experience psychological perversion he cannot remain disjointed and can find a solution through ethics and morality.